Exploring STEM with a focus on engineering and creativity in an early childhood setting - Oblak, Chloe (Curtin University, 2022)
This study investigated the effect of the STEM engineering design process on young children’s creativity. Through Action Research, young children aged three and four years old were observed in an early childhood setting, engaging in their everyday play. An engineering design process was implemented in two action cycles. As a result, the children demonstrated an increase in engagement, characteristics of creativity, and overarching social and emotional capabilities were enhanced, as well as educator pedagogy.